Impaired Mitophagy Plays a Role in Denervation of Neuromuscular Junctions in ALS Mice - Rogers, Robert S.; Tungtur, Sudheer; Tanaka, Tomohiro; Nadeau, Lisa L.; Badawi, Yomna; Wang, Hua; Ni, Hong-Min; Ding, Wen-Xing; Nishimune, Hiroshi (Frontiers in Neuroscience, 2017)
Motor neurons in amyotrophic lateral sclerosis (ALS) patients and animal models show degeneration from the nerve terminal, known as dying-back neuropathy. To investigate the mechanism underlying this neuropathy, we analyzed the neuromuscular junctions (NMJs) and motor neuron cell bodies in SOD1G93A mice using electron microscopy. NMJs of SOD1G93A mice exhibited significantly higher numbers of autophagosomes and degenerated mitochondria compared to wild-type controls. Mitophagosomes were identified in the NMJ presynaptic terminals of wild-type mice and SOD1G93A mice. However, the number of mitophagosomes did not increase significantly in SOD1G93A NMJs indicating a defect in mitophagy, the autophagic process to degrade mitochondria. Consistent with this, proteins essential for mitophagy, p62/SQSTM1, Bnip3, Pink1, and Parkin were down-regulated in motor neurons in SOD1G93A mice. Importantly, SQSTM1 is one of the genes mutated in familial ALS patients. We evaluated the effect of impaired mitophagy on motor neurons by analyzing the double knockout mice of Pink1 and Parkin, two genes responsible for sensing depolarized mitochondria and delivering degenerated mitochondria to mitophagosomes. The double knockout mice exhibited NMJ degeneration, including axon swelling and NMJ fragmentation at four months of age. These phenotypes are rarely observed in wild-type control mice of the same age. The protein level of ATP synthase β subunit increased in the NMJ presynaptic terminals, suggesting the accumulation of mitochondria at NMJs of the double knockout mice. Importantly, NMJ denervation was observed in the double knockout mice. These data suggest that the reduced mitophagy function in motor neurons of SOD1G93A mice is one of the mechanisms causing degeneration of ALS NMJs.